OpenSR: An Open-Source Stimulus–Response Testing Framework - Matheus, Carolyn; Svegliato, Justin (Human Technology, 2015)
Stimulus–response (S–R) tests provide a unique way to acquire information about human perception by capturing automatic responses to stimuli and attentional processes. This paper presents OpenSR, a user-centered S–R testing framework providing a graphical user interface that can be used by researchers to customize, administer, and manage one type of S–R test, the implicit association test. OpenSR provides an extensible open-source Web-based framework that is platform independent and can be implemented on most computers using any operating system. In addition, it provides capabilities for automatically generating and assigning participant identifications, assigning participants to different condition groups, tracking responses, and facilitating collecting and exporting of data. The Web technologies and languages used in creating the OpenSR framework are discussed, namely, HTML5, CSS3, JavaScript, jQuery, Twitter Bootstrap, Python, and Django. OpenSR is available for free download.